Teacher Strategies in Cultivating Empathy and Sympathy in Students at State Junior High School 7 Muaro Jambi - Rosalinda, Mira; Fahri, Ismail; Saputra, Edi (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2026)
Empathy and sympathy are essential elements in character development and social harmony, especially during adolescence. In the context of education, Islamic Religious Education (PAI) plays a strategic role in instilling these values thru learning integrated with Islamic moral and social teachings. However, at SMP Negeri 7 Muaro Jambi, low levels of empathy and sympathy were still found among 7th-grade students, as reflected in their lack of caring behavior and weak positive social interaction. This study aims to analyze teachers' strategies in fostering empathy and sympathy among seventh-grade students thru Islamic Religious Education (PAI) lessons. This study uses a qualitative approach with a case study design. Data were obtained thru observation, interviews, and documentation, which were then analyzed descriptively thru data reduction, data presentation, and conclusion drawing processes. The research findings indicate that PAI teachers employ several key strategies, namely modeling attitudes, cultivating positive social behaviors, discussions and group work, integrating Islamic values into learning materials, and a personal approach to students. These strategies have been proven to foster the development of empathy and sympathy in students, as demonstrated by their caring attitude, mutual respect, helpfulness, and ability to understand the feelings of others in school life.